2015 AIChE Spring Meeting & 11th Global Congress on Process Safety : perspectives on process safety from around the world (Center for Chemical Process Safety/AIChE, 2015)
This book from Around the World is consists of sessions that strives to provide a space for different regions around the world to get together at the Global Congress and discuss the issues that are significantly impacting the development in Process Safety in their regions, considering the particular needs of language, and cultural characteristics of each one. --